Pengaruh Segmentasi Pasar Dan Perilaku Konsumen Terhadap Keputusan Pembelian - Fitri; Fitri Fitri; Yusran Paris (BJRM (Bongaya Journal of Research in Management), 2026)
This research utilizes a quantitative approach. The population in this research is consumers who carry out the purchase of motorcycles at PT Suracojaya Abadi Motor, Luwu Regency. The sampling technique was carried out using the Slovin formula and an error tolerance rate of 10%, so that the number of respondents was 95 people. Data was collected through questionnaires, then analyzed using multiple linear regression with the help of SPSS software version 25. The results of this research show that Market Segmentation has a Partial Significant Influence on Purchase Decisions with a t-value of 3.204. Consumer Behavior also has a Partial Significant Effect on Purchase Decisions with a t-value of 3.566. Simultaneously, these two independent variables affect the Purchase Decision, with an F-count value of 10.435. Keywords: Market Segmentation, Consumer Behavior, and Purchasing Decisions